Modelling the extrusion cooling/calibration stage for complex thermoplastic profiles - Ribau, A. M. (2012)
The main objective of this work is to implement a 3D non-isothermal multi-domain numerical code, based on finite volume method, able to deal with unstructured meshes that can be used to aid the design of calibration/cooling systems. At the final stage the code should incorporate the major phenomena that take place during profile cooling, including the prediction of the developed thermal residual stresses.